Frequency of ventricular tachyarrhythmias in patients with different risk scores for sudden cardiac death in hypertrophic cardiomyopathy and cardioverter defibrilators implanted in primary prevention. (24th May 2021) - Brankovic, N; Radovanovic, NN; Vujadinovic, N; Kircanski, B; Sajic, V; Milasinovic, A; Zivkovic, M; Bisenic, V; Pavlovic, SU; Milasinovic, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The European Society of Cardiology's (ESC) risk calculator for sudden cardiac death (SCD) in patients with hypertrophic cardiomyopathies (HCM) is currently a tool that facilitates the decision to implant a cardioverter defibrillator (ICD) in primary prevention, but doubts still exist in everyday clinical practice. Purpose: We aimed to determine the incidence of life-threatening ventricular arrhythmias during long-term follow-up in patients with different ESC HCM risk scores for SCD calculated on ICD implantation in primary prevention. Methods: This retrospective, observational study was conducted in a tertiary center among adult patients with HCM and ICD devices (ICD-VR, ICD-DR and CRT-ICD) implanted in primary prevention from January 2008 to December 2019. The patients followed up for less than one year were excluded from the analysis. Study group was divided into three subgroups, according to the ESC 5 years risk score of SCD and based on it the estimated need for ICD implantation: group A with risk < 4%, where ICD is generally not indicated; group B with risk 4-6%, where ICD may be considered; group C with risk ≥6%, where ICD should be considered. Regularly, ICD was interrogated twice a year, while emergency controls were performed after delivering of ICD therapy. Follow-up data including information about sustained ventricular tachicardia (VT) and ventricular fibrillation (VF) episodes were collected from patients medical records. Results: In the observed period, ICD devices were implanted in 60 adult patients with HCM. Ten of them had history of sustained ventricular arrhythmias and 3 were lost to follow-up. Therefore, we analysed 47 patients (55.3% male, mean age 51.0 ± 15.7 years), 13 from group A, 12 from group B and 22 from group C. Mean follow-up period was 80.6 ± 37.9 months. During the follow-up period ventricular tachyarrhythmias (VT and VF, either in monitoring or therapy zone) were recorded in one patient from group A (7.7%), in two patients from group B (16.7%) and in 7 patients from group C (31.8%). Using Kruskal-Wallis analysis of variance, we did not find a statistically significant difference in the occurrence of ventricular tachyarrhythmias among the observed groups (p = 0.225). Conclusions: Patients with HCM and a 5-year risk of SCD ≥ 6% calculated on ICD implantation had more frequent life-threatening ventricular arrhythmias during long-term follow-up, but not statistically significant. There should be an individual approach when deciding on the need for device implantation in all patients with HCM.